Vaccine acceptance among adult population in developed democratic western countries : Barriers to vaccine acceptance in the adult population of mainland Finland, 2021 - Lasander, Mervi (My University, 2024)
This master’s thesis consists of two parts: a theoretical background and scientific article titled ‘Barriers to vaccine acceptance in the adult population of mainland Finland, 2021’, published in the international peer-reviewed journal, authored by Mervi Lasander, Kimmo Elo, Katja Joronen and Timothée Dub. The subject of the thesis is adult vaccine acceptance in developed democratic western countries, particularly in Europe. The objective of the study is to describe and explain vaccine acceptance among Finnish adults in 2021 and to investigate the multidimensional factors underlying vaccine acceptance, for which there is limited previous research data on vaccination in general. Vaccine acceptance refers to a positive response to vaccination, whereas vaccine hesitancy to a critical attitude. The World Health Organization (WHO) ranked the vaccine hesitancy as one of the top ten health threats in the world in 2019. Social phenomena influence perceptions of vaccination through health communication and information; thus, a multidimensional approach is required to study the attitudes, opinions, beliefs, and experiences that underlie vaccine acceptance. The data of the study was extracted from the Medicines Barometer 2021 survey conducted by the Finnish Medicines Agency (Fimea) and include the perceptions of 2,081 Finnish adults on medicines and vaccines (response rate 20.6%). Associations with vaccine acceptance were statistically analysed using Chi square tests and logistic regression, with an Odds Ratio of 95% confidence intervals, and explorative factor analysis (EFA). Statistical tests were performed using R software 4.2.2. The results showed that the majority of respondents considered vaccines to be safe (93%), important (95%) and effective (97%). However, 20% and 14% felt they did not have enough information about vaccines and vaccine-preventable diseases (VPDs), respectively. Respondents aged 18-39 were 2.8 times more likely to disagree that they had enough information about vaccines than respondents aged 60-79 (p<0.001), while respondents with poorer self-perceived health were 1.8 times more likely than others to declare not having enough information about vaccines (p<0.001). Three factor dimensions were created from the eight EFA statements: ‘Confidence and attitudes towards vaccines,’ ‘Access to information on vaccines and VPDs’ and ‘Debate on vaccination issues.’ Vaccine acceptance is constantly changing among people. Understanding the root causes of vaccine acceptance and hesitancy provides knowledge to support health care policy and development. The availability and accessibility of vaccination information among Finnish adults needs to be improved in order to prevent the spread of VPDs by promoting the vaccine acceptance.

Tämä maisterin tutkielma koostuu kahdesta osasta: teoreettisesta taustasta ja tieteellisestä artikkelista ’Barriers to vaccine acceptance in the adult population of mainland Finland, 2021’, joka on julkaistu kansainvälisessä vertaisarvioidussa lehdessä, ja jonka on kirjoittanut Mervi Lasander, Kimmo Elo, Katja Joronen ja Timothée Dub. Tutkielman aiheena on aikuisten rokotehyväksyntä kehittyneissä demokraattisissa länsimaissa, erityisesti Euroopassa. Tutkimuksen tarkoituksena on kuvata ja selittää suomalaisten aikuisten rokotehyväksyntää vuonna 2021, sekä selvittää rokotehyväksynnän taustalla olevia moniulotteisia tekijöitä, joista on rajoitetusti aiempaa tutkimustietoa yleisesti rokotusten osalta. Rokotehyväksyntä tarkoittaa myönteistä suhtautumista rokotuksiin, kun taas rokote-epäröinti kriittistä asennetta. Maailman terveysjärjestö (WHO) lisäsi rokote-epäröinnin maailman kymmenen suurimman terveysuhan listaan vuonna 2019. Yhteiskunnalliset ilmiöt vaikuttavat rokotuskäsityksiin terveysviestinnän ja -tiedon kautta, siten moniulotteinen lähtökohta rokotehyväksynnän taustalla vaikuttavien asenteiden, mielipiteiden, uskomusten ja kokemusten tarkasteluun on tarpeellinen. Tutkimuksen aineisto on poimittu lääkealan turvallisuus- ja kehittämiskeskus Fimean Lääkebarometri 2021 kyselystä, ja sisältää 2081 aikuisen suomalaisen käsityksiä lääkkeistä ja rokotuksista. Yhteyksiä rokotehyväksyntään analysoitiin tilastollisesti Khin neliö -testien ja logistisen regression avulla käyttäen kertoimen suhdelukua 95 % luottamusvälillä, sekä eksploratiivisen faktorianalyysin (EFA) avulla. Tilastolliset testit suoritettiin R-ohjelmalla 4.2.2. Tulokset osoittivat, että suurin osa vastaajista piti rokotteita turvallisina (93 %), tärkeinä (95 %) ja tehokkaina (97 %). Kuitenkin 20 % ja 14 % vastaajista koki, ettei heillä ollut riittävästi tietoa rokotteista ja rokotteilla ehkäistävistä taudeista. 18-39-vuotiaat vastaajat olivat 2,8 kertaa todennäköisemmin eri mieltä siitä, että heillä oli riittävästi tietoa rokotuksista, verrattuna 60-79-vuotiaisiin (p<0.001), ja terveydentilansa heikommaksi kokevat vastaajat ilmoittivat 1,8 kertaa muita todennäköisemmin, ettei heillä ollut riittävästi tietoa rokotteista (p<0.001). Kahdeksasta EFA väittämästä luotiin kolme faktoriulottuvuutta: ’Luottamus ja asenteet rokotteita kohtaan’, ’Rokotteita ja tartuntatauteja koskevan tiedon saatavuus’ ja ’Rokotuskysymyksiä koskeva keskustelu’. Rokotehyväksyntä ilmiönä muuttuu jatkuvasti ihmisten keskuudessa. Rokotehyväksynnän ja -epäröinnin perimmäisten syiden ymmärtäminen tuottaa tietämystä terveydenhuollon ohjauksen ja kehittämisen tueksi. Rokotuksia koskevan tiedon saatavuutta ja saavutettavuutta tulee parantaa tartuntatautien leviämisen ehkäisemiseksi edistämällä rokotehyväksyntää.
Keywords: attitudes, health policy, survey, vaccine acceptance, vaccine hesitancy